Promoting Teacher Engagement with Assessment for Learning through a Flipped CPD-based Community of Practice - KELLOUGH, JILLIAN MARIE (Trinity College Dublin. School of Education. Discipline of Education, 2018)
Education systems are increasingly characterised by continuous cycles of reform. In the Republic of Ireland, recent reform of Junior Cycle aims to modify assessment structures and practices. This study describes a small-scale initiative to support teachers’ assessment literacy through an innovative model of continuing professional development (CPD). Recognising challenges posed by time constraints in schools and the need to optimise practising of assessment skills by teachers in real time, this approach offered potential solutions to age-old problems in CPD. Informed by research on Flipped Learning and Flipped Leadership (Bergmann & Sams, 2012; Conley, 2013; DeWitt, 2014; FLN, 2014) this research study engaged participants in Flipped CPD; a teacher learning model that offered an alternative approach to CPD by positioning the traditional social structure of a community of practice within an online community through engagement in an interactive, interdisciplinary platform. An evaluative case study was employed to frame a developmental programme evaluation, exploring the impact of a bespoke program of Flipped CPD on teachers’ implementation and integration of AfL and overall professional growth. The case study aimed to work with a group of ten teachers of first and/or second year classes at Junior Cycle, across two school communities, from four subject areas: Business Studies, Geography, Mathematics, and Science. A concurrent mixed methods approach was used to address the research objectives and provide a comprehensive analysis through data source triangulation, thus allowing the researcher to view how educators from different subject areas and teaching experience engaged within the same CPD model. By utilising a wealth of data collection methods this study was able to establish key findings associated with each of the three-research question. Through a thematic analysis the study was able to identify four themes associated with enabling and disenabling characteristics of AfL practice: promoting student engagement, identifying meaningful strategies, experienced challenges to AfL’s implementation in Mathematics, and coherence of practice across AfL features. Additionally, through teachers’ engagement in Flipped CPD the study was able to identify themes highlighting both benefits and limitations to the CPD model: interdisciplinary collaboration, teacher autonomy, and engaging in critical friendships. Key findings from these themes were used to determine to what degree teachers’ involvement in Flipped CPD might have influenced their AfL practice. Flipped CPD provided teachers flexibility, an opportunity to contribute to CPD content and personalise their learning, as well as engage in continuous support from a community of peers. While the research and development of an innovative model for CPD became a focal point of this research study, its driving force was and remains the proposed reform to assessment practices at Junior Cycle and teachers’ integration of AfL. The search for resources and models of professional development to facilitate and promote AfL practice continues. Flipped CPD served as not only a vehicle to address this need, but as an opportunity to explore the assessment practices of teachers and students in Ireland’s post-primary schools, specifically in the implementation of effective AfL practice.
APPROVED
Keywords: Teacher Professional Development, Flipped Learning, Community of Practice, Assessment for Learning, Formative Assessment, Junior Cycle Reform